Design and Implementation of an Air Pollution Monitoring System in the Campus Area of Politeknik Negeri Lhokseumawe - Indrawati, Indrawati; D, Amir (Politeknik Negeri Lhokseumawe, 2025)
Air pollution is a significant environmental issue that directly affects human health, especially in high-activity areas such as university campuses. This study aims to design and implement a real-time air pollution monitoring system in the campus area of Politeknik Negeri Lhokseumawe. The system utilizes MQ135 and MQ7 gas sensors to detect CO₂ and CO levels in both indoor and outdoor environments. Sensor data are processed using a microcontroller and displayed through a web-based application interface to facilitate user-friendly monitoring. System testing was conducted by recording sensor readings in various environmental conditions over specific time intervals. The test results show that the system can distinguish pollution levels between indoor and outdoor settings and provides data that are relatively stable and responsive to changes in air quality. The implementation of this system is expected to support the campus in monitoring and managing air quality effectively. The normal indoor CO₂ level is 400–800 ppm while the MQ135 shows 325, which means the monitoring system is acceptable and reasonable. For CO . the normal condition is 10 ppm, but the analog MQ7 can show relative values; if it goes up and down according to the trend, it can be accepted as a relative indicator.